Bestimmung der Augenlinsen - exposition bei Patienten nach einer Radioi odtherapie - Andreeff, M.; Claußnitzer, J.; Oehme, L.; Freudenberg, R.; Kotzerke, J. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: Current reports for the radiation cataracts contained a warning for deterministic effects at 1–2 Gy radiation single exposure for lens. Recently, the German Radiation Protection Board (SSK) published a document (234. SSK-Board) in that threshold dose for radiation cataracts is claimed at 0.5 Gy. The lens of the eye is recognized as one of the most radiosensitive tissues in the human body, and the International Commission on Radiological Protection (ICRP 103) has defined a limit of 150 mSv for its exposure. Recently, the ICRP lowered this limit down to 20 mSv per year. However, this limit does not apply to patients. Therefore, the question of the lens radiation exposure for patients underwent a radioiodine therapy (RIT) is a point at issue. Patients, methods: A total of 41 patients (age: 22–92 years) underwent a radioiodine therapy were included in the study. Optical stimulated luminescence dosimeters were used to measure the radiation exposure. The dosimeters were fastened nearby the patient’s eye lens. The measurement was carried out up to 48 h after radioiodine application and the patients were divided into three groups. Group 1: patients underwent a diagnostic 131I whole body scan (mean activity: 370 MBq); group 2: thyriod carcinoma patients under RIT (mean activity: 3700 MBq); group 3: hyperthyroid patients under RIT (activity: 180–1237 MBq). Results: The cumulative exposure of the eye lens during the stay at the therapy unit (48 h) was 4.8 ± 0.7 mGy in group 1, 24.5–50.5 mGy in group 2 and 2.7–26.3 mGy in group 3, respectively. For the calculation of the expected cumulative dose, including follow-up after patient's dismissal, the effective half-lives were involved. The cumulative doses were obtained to be 6 ± 1 mGy in the first group, 63 ± 15 mGy in the second and 5–148 mGy in the third. Conclusion: The results show that there exists a low risk for radiation cataract in a nuclear medicine therapy unit. After serial radioiodine therapies radiation-induced lens opacity cannot be expected.
Keywords: Ocular lens; radioiodine therapy; cataract; dosimetry